2019
DOI: 10.4034/pboci.2019.191.49
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Medical and Dental Iranian Students about the Infection and Vaccination of Human Papilloma Virus

Abstract: Objective: To evaluate awareness of medical and dental students of Kerman University of medical science about the infection and vaccination of the human papilloma virus. Material and Methods: This descriptive cross-sectional study was conducted on 290 medical and dental students. The data were collected using a questionnaire, which consisted of demographic data, and awareness-raising questions whose validity and reliability were confirmed. Mann-Whitney U and linear regression test were used for statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The finding of this study indicated that most than half of the study participants had good awareness/knowledge about the HPV infection and its vaccine. This finding is consistent with the studies conducted in Iran [17,18], Iraq [19] and India [20]. However, this finding is higher than the studies done in Malaysia [21] and Turkey [22].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of this study indicated that most than half of the study participants had good awareness/knowledge about the HPV infection and its vaccine. This finding is consistent with the studies conducted in Iran [17,18], Iraq [19] and India [20]. However, this finding is higher than the studies done in Malaysia [21] and Turkey [22].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, 57.5% did not know that HPV infection could cause cervical cancer. Similarly, low level of HPV knowledge and cervical cancer knowledge in South Asian immigrant women were reported in a recent investigation (35). Overall, cervical cancer incidence in low-income countries is high and should be provide more HPV education as a high priority.…”
Section: Discussionmentioning
confidence: 63%
“…They found that 48.7% of students declared to be vaccinated against HPV and that 57.7% of female students and 27.7% of male students reported to be vaccinated. Hashemıpour et al (9) conducted questionnaire on 290 medical and dental students to evaluate awareness of medical and dental students about the infection and vaccination of the human papilloma virus. In their study, 39.9% of respondents were not familiar with the HPV vaccine and 62.1% tended to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus (HPV) leads to approximately 72% of male and 63% of female oropharyngeal cancers (8). It has been reported that HPV is responsible for 91% of anal cancers, 75% of vaginal cancers and 60% of oropharyngeal cancers in the United States (9). While oral cancer rates are growing overall, HPV-related oral cancer is rising undoubtfully and requires a prevention attempts focused on HPV (10).…”
Section: Introductionmentioning
confidence: 99%